Vers la systématisation des lois québécoises - Issalys, Pierre (Les Cahiers de droit, 1980)
The object of this paper is to suggest means whereby the body of statute law could be rearranged into a systematic whole. The concept of a system of statutes is first defined and contrasted with the concept of codification. Systematization is presented as involving two stages. First, a classification grid is obtained by grouping statutes under a number of broad headings according to their subject-matter. Second, within each group the various statutory provisions are ranked and possibly rearranged according to the scope of their application within the field covered by the group of statutes as a whole. While statutes retain individual existence, logical links between them are made more explicit. The concept is then applied experimentally to a group of 23 Québec statutes dealing with the provincial Cabinet and the organization of government departments. Proposals are thus made for a new Government Organization Act and new statutes setting up each of the departments. The paper then considers extending the process of systematization to a larger group including all statutes setting up agencies of the Québec government (administrative tribunals, regulatory boards, Crown corporations, etc.). This, it is suggested, could lead to the adoption by stages of a Code of Government Organization. Finally, the paper examines the requirements of the systematization of statutes as to legislative draftsmanship, legislative policy, and the legislative process. It argues for the need for a new agency with responsibility to advise the government on draft legislation and to carry out the systematization of groups of statutes on request from the National Assembly.